In-hospital cardiac arrest in critically ill patients with covid-19: multicenter cohort study. (30th September 2020) - Hayek, Salim S; Brenner, Samantha K; Azam, Tariq U; Shadid, Husam R; Anderson, Elizabeth; Berlin, Hanna; Pan, Michael; Meloche, Chelsea; Feroz, Rafey; O'Hayer, Patrick; Kaakati, Rayan; Bitar, Abbas; et al.
Abstract: Objectives: To estimate the incidence, risk factors, and outcomes associated with in-hospital cardiac arrest and cardiopulmonary resuscitation in critically ill adults with coronavirus disease 2019 (covid-19). Design: Multicenter cohort study. Setting: Intensive care units at 68 geographically diverse hospitals across the United States. Participants: Critically ill adults (age ≥18 years) with laboratory confirmed covid-19. Main outcome measures: In-hospital cardiac arrest within 14 days of admission to an intensive care unit and in-hospital mortality. Results: Among 5019 critically ill patients with covid-19, 14.0% (701/5019) had in-hospital cardiac arrest, 57.1% (400/701) of whom received cardiopulmonary resuscitation. Patients who had in-hospital cardiac arrest were older (mean age 63 (standard deviation 14) v 60 (15) years), had more comorbidities, and were more likely to be admitted to a hospital with a smaller number of intensive care unit beds compared with those who did not have in-hospital cardiac arrest. Patients who received cardiopulmonary resuscitation were younger than those who did not (mean age 61 (standard deviation 14) v 67 (14) years). The most common rhythms at the time of cardiopulmonary resuscitation were pulseless electrical activity (49.8%, 199/400) and asystole (23.8%, 95/400). 48 of the 400 patients (12.0%) who received cardiopulmonary resuscitation survived to hospital discharge, and only 7.0% (28/400) survived to hospital discharge with normal or mildly impaired neurological status. Survival to hospital discharge differed by age, with 21.2% (11/52) of patients younger than 45 years surviving compared with 2.9% (1/34) of those aged 80 or older. Conclusions: Cardiac arrest is common in critically ill patients with covid-19 and is associated with poor survival, particularly among older patients.